"USING NEWSPAPERS AND SOCIAL MEDIA POSTS AS AUTHENTIC READING MATERIALS FOR B1-B2 LEARNERS" (International Conference on Modern Science and Scientific Studies, 2025)
The role of media in the economic and social development of Uzbekistan is of great importance. Today, newspaper and social media platforms have become an integral part of society's life, serving not only as a quick delivery of news, but also as an important function in shaping people's opinions and views. Newspaper and social media provide readers with complete and accurate information about real events, as well as expanding their worldview, increasing the range of knowledge and thinking. The rapid and efficient dissemination of information is an important factor in the further development of society.